An attempt at an objective method for differential diagnosis of dysphonias - Jayaram K (Journal of All India Institute of Speech and Hearing, 1970)
The present study was concerned with obtaining norms for both males and females on some of the parameters related to voice and to compare these findings with those obtained for various dysphonics. It was also aimed to see if any significant differences are seen among several clinical types of dysphonias.